Mental health and well‐being impacts of COVID‐19 on rural paramedics, police, community nurses and child protection workers. (29th September 2021) - Roberts, Russell; Wong, Alfred; Jenkins, Stacey; Neher, Alain; Sutton, Clare; O'Meara, Peter; Frost, Mark; Bamberry, Larissa; Dwivedi, Abhishek
Abstract: Objective: To investigate the impact of COVID‐19 on the mental health and well‐being of rural paramedics, police, community nursing and child protection staff. Method: An online survey was distributed to investigate the sources of stress and support across individual, task and organisational domains. Setting and Participants: The survey was completed by 1542 paramedics, police, community nurses and child protection workers from all states and territories of Australia. This study describes the data for the 632 rural participants. Main outcome measures: The main measures of well‐being were the Public Health Questionnaire (PHQ9), the Generalised Anxiety Disorder (GAD7), the Maslach Burnout Inventory (MBI), workplace engagement, intention to quit and COVID‐19–related stress. Results: The mean depression and anxiety scores were 8.2 (PHQ9) and 6.8 (GAD7). This is 2–3 times that found in the general community. Over half (56.1%) of respondents showed high emotional exhaustion (burnout). The emotional exhaustion, depersonalisation and personal accomplishment mean scores were 28.5, 9.3 and 34.2, respectively. The strongest associations with burnout and psychological distress were workload, provision of practical support, training and organisational communication. A significant proportion of respondents were seriously considering quitting (27.4%) or looking for a new job with a different employer (28.5%) in the next 12 months. Conclusions: COVID‐19 has increased the workload and stress on rural front‐line community staff. The major sources of stress were related to organisations' responses to COVID‐19 and not COVID‐19 per se. The data suggest the most effective mental health interventions are practical and preventive, such as firstly ensuring fair and reasonable workloads.